A practical guide to the management of immune thrombocytopenia co-existing with acute coronary syndrome - Rahhal, Alaa; Provan, Drew; Ghanima, Waleed; González-López, Tomás José; Shunnar, Khaled; Najim, Mostafa; Ahmed, Ashraf Omer; Rozi, Waail; Arabi, Abdulrahman; Yassin, Mohamed (Frontiers in Medicine, 2024)
Immune Thrombocytopenia (ITP) management with co-existing Acute Coronary Syndrome (ACS) remains challenging as it requires a clinically relevant balance between the risk and outcomes of thrombosis and risk of bleeding. However, the literature evaluating the treatment approaches in this high-risk population is scarce. Thus, in this review, we aimed to summarize the available literature on the safety of ITP first and second line therapies to provide a practical guide on the management of ITP with co-existing ACS. We advise to hold antithrombotic therapy, including antiplatelet agents and anticoagulation in severe thrombocytopenia with platelet count <30 ×10 9 /L, and to use a single antiplatelet agent when platelet count falls between 30-50 ×10 9 /L. We provide a step-wise approach according to platelet count and response to initial therapy, starting with corticosteroids, with or without intravenous immunoglobulin (IVIG) with a dose limit of 35 g, followed by a thrombopoietin receptor agonist (TPO-RA) to a target platelet count of 200 ×10 9 /L, then rituximab. Our review may serve as a practical guide for clinicians in the management of ITP co-existing with ACS.